Tribocorrosion Behaviour of Ti6Al4V Produced by Selective Laser Melting for Dental Implants - Vilhena, Luis M. (2020)
Additively produced Ti6Al4V implants display mechanical properties that are economically infeasible to achieve with conventional subtractive methods. The aim of the present research work was to characterize the tribocorrosion behaviour of the newly produced Ti6Al4V, also known as titanium grade 5, by a selective laser melting (SLM) technique and compare it with another specimen produced by a conventional method. It was found that the tribological properties were of the same order, with the wear rate being k= 6.3 104 mm3/N m and k = 8.3 104 mm3/N m for respectively, SLM and conventional method. Regarding the friction behaviour, both methods exhibited similar COF in the order of 0.41–0.51. However, electrochemically, the potentiodynamic polarization curves presented some di erences mainly in the potential range of the passive films and passive current density formed, with the passive current density being lower for the SLM method.